2021
DOI: 10.1016/j.fertnstert.2020.10.059
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, assessor-blind, antimüllerian hormone–stratified, dose-response trial in Japanese in vitro fertilization/intracytoplasmic sperm injection patients undergoing controlled ovarian stimulation with follitropin delta

Abstract: Objective: To establish the relationship between follitropin delta doses (recombinant follicle-stimulating hormone produced from the human cell line PER.C6) and ovarian response in Japanese women undergoing in vitro fertilization/intracytoplasmic sperm injection treatment and to evaluate the influence of initial antim€ ullerian hormone (AMH) levels. Design: Randomized, controlled, assessor-blind, AMH-stratified (low 5.0-14.9 pmol/L; high 15.0-44.9 pmol/L) dose-response trial. Setting: Reproductive medicine cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 15 publications
2
24
0
Order By: Relevance
“…In the present trial, conventional dosing was associated with an incidence of 19.8% for OHSS and 14.1% for moderate/severe OHSS. This is consistent with previous clinical trials in Japan reporting OHSS rates of 20-22% (Fujiwara, 2015;Ishihara et al, 2020a). The 50% reduction in occurrence of OHSS (11.2%) and moderate/severe OHSS (7.1%) with the individualised dosing approach is therefore clinically relevant and a major improvement for the patients' safety.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In the present trial, conventional dosing was associated with an incidence of 19.8% for OHSS and 14.1% for moderate/severe OHSS. This is consistent with previous clinical trials in Japan reporting OHSS rates of 20-22% (Fujiwara, 2015;Ishihara et al, 2020a). The 50% reduction in occurrence of OHSS (11.2%) and moderate/severe OHSS (7.1%) with the individualised dosing approach is therefore clinically relevant and a major improvement for the patients' safety.…”
Section: Discussionsupporting
confidence: 90%
“…In line with the RCT conducted outside Japan (Nyboe Andersen and Nelson et al, 2017), the present trial also showed that efficacy in terms of pregnancy and live birth rates was not compromised with individualised dosing. The live birth rates of 23.5% for individualised dosing and 18.6% for conventional dosing in Japanese IVF/ICSI patients are in line with the observations made in previous clinical trials conducted in Japan (Follistim, 2015;Ishihara et al, 2020a) and also with what is reported from clinical practice in Japan (Ishihara et al, 2020b).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Comprehensive clinical trials have been performed in in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) patients undergoing ovarian stimulation to document the efficacy and safety of follitropin delta versus CHO-derived recombinant FSH preparations [8][9][10][11][12][13]. The trials have mainly focused on fresh cycles and have provided reassuring information on follitropin delta with respect to the clinical performance of fresh blastocysts leading to pregnancy and live birth as well as the safety of the patients.…”
Section: Introductionmentioning
confidence: 99%